2016
DOI: 10.1088/0964-1726/25/10/104004
|View full text |Cite
|
Sign up to set email alerts
|

Experimental characterization and modeling of a three-variant magnetic shape memory alloy

Abstract: Researchers have attempted to characterize and predict the magneto-mechanical behavior of magnetic shape memory alloys (MSMAs) for over a decade. However, all prior experimental investigations on MSMA have been performed on samples accommodating two martensite variants and generally the MSMA is only exposed to two-dimensional magneto-mechanical loading. As efforts have been underway to develop models able to predict the most general (i.e. 3D) loading conditions for MSMAs with three-varints, there is also a nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
(13 reference statements)
1
12
0
Order By: Relevance
“…Additional discrepancies between the theoretical and experimentally observed average output voltage may be because we do not account for changes in H in our theoretical calculations. Feigenbaum et al (2016) measure approximately 20% higher field when the easy axis is aligned with the field as compared to when the hard axis is aligned with the external field. This change in H is due to change in demagnetization.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Additional discrepancies between the theoretical and experimentally observed average output voltage may be because we do not account for changes in H in our theoretical calculations. Feigenbaum et al (2016) measure approximately 20% higher field when the easy axis is aligned with the field as compared to when the hard axis is aligned with the external field. This change in H is due to change in demagnetization.…”
Section: Discussionmentioning
confidence: 97%
“…We have seen this asymmetry in the Ni-Mn-Ga MSMAs before. In order to fit experimental data, both LaMaster et al (2014) and Feigenbaum et al (2016) proposed models with asymmetric hardening functions, which suggested that the material behaves differently when going from V 1 to V 2 than viceversa. This asymmetry is still not well understood, but is confirmed by the data in this work.…”
Section: Discussionmentioning
confidence: 99%
“…Surface constraints can be created by surface treatments and external forces, including fixturing and the Maxwell force which attracts the ferromagnetic element to the magnet. The actuation mechanism of the MSM element is thus complex [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…When the material is placed in a magnetic field, the magnetization vectors begin to rotate to align with the external field to minimize the potential energy of the material. However, the magnetization vectors are relatively difficult to rotate in MSMAs [4][5][6]. As a consequence, magnetic fields of adequate strength will cause the variants to reorient in order to more efficiently align the internal magnetization vectors with the external field [6,7] (figure 2 right, bottom).…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have attempted to do this (e.g. [4,7,[10][11][12][13][14][15][16]) however, there is lack of clarity in the literature regarding how to account for the material's demagnetization, both experimentally and in models.…”
Section: Introductionmentioning
confidence: 99%